Modelling, simulation and control of two-wheeled vehicles - Savaresi, Sergio M.; Tanelli, Mara; Corno, Mauro 1970- (Automative series, 2014)
This book discusses all aspects of two-wheeled vehicles, comprehensively covering the main methods, tools and approaches to address the modelling, simulation and control design issues. It also offers a perspective on the future trends in the field, outlining the challenges and the industrial and academic development scenarios. Extensive reference to real-world problems and experimental tests is also included throughout.